Quantifying Interdisciplinarity: Connections@Illinois - Rudasill, Lynne M.; Shreeves, Sarah (Qualitative and Quantitative Methods in Libraries; Vol 2 No 3 (2013): September 2013 Issue, 2017)
Interdisciplinary approaches must become predominant in the area of problem-solving for successful policy development to treat the issues we are facing in a highly globalized world.  Recent publications on the topic of interdisciplinary studies argue that we are seeing an expansion in these areas of research.  This paper explores several methods by which the librarian and information scientist can assess the growth of interdisciplinary studies, both at their institutions and in the academy as a whole.  We will explore several recent studies in the area and introduce tools that we are using to determine who is publishing where and with whom to better understand the evolution of interdisciplinary studies.